Electrokinetic blood flow of Carreau ternary nanofluids in stenotic arteries with thermal reactions under CC heat flux for therapy - Saima Riasat; Saira Iqbal; Sadia Hina; Kaouther Ghachem; Aboulbaba Eladeb; Walid Hassen; Lioua Kolsi (Scientific Reports)
Abstract This study provides valuable insight into developing more accurate blood-flow models for targeted drug delivery and therapeutic heat management in stenosed arteries by focusing on the synergistic effects of electrokinetic forces and thermal-chemical interactions. The aim is to investigate electroosmotic flow and endothermic/exothermic chemical reactions within a constricted artery by incorporating the Cattaneo–Christov (CC) heat flux model into a Carreau ternary hybrid nanofluid framework. The governing equations are solved computationally using the BVP4C solver. The main results indicate that the increase of the zeta potential (electrokinetic effect) causes a substantial reduction of the wall shear stress, which lowers energy losses and improves overall blood flow efficiency. In addition, at high electroosmotic parameter the fluid is accelerated, and an enhancement of drug delivery precision and therapeutic effectiveness occur. The model also predicts a modest ~ 7% increase in drag force on the arterial wall under these conditions. Conclusion: Integrating electrokinetic forces and thermal-chemical effects into blood-flow modeling significantly improves flow efficiency and targeted delivery in stenotic arteries, highlighting a promising strategy for optimizing nanoparticle-based treatments.